PENGARUH NARASI PRODUK DAN FOTO PRODUK TERHADAP PRESEPSI KUALITAS DAN MINAT BELI WISATAWAN MELALUI PORTAL DIGITAL AGODA - Agung Sulistyo; Suhartapa Suhartapa; Rosalina Nur Annisa (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2022)
The development of digital technology has forced tourism industry players to adopt various digital platforms. This study aims to test the effectiveness of the AGODA digital portal as a marketing channel. This research was conducted to complement previous research on other digital portals such as tiket.com, traveloka, and several other portals. The quantitative research design was carried out by distributing questionnaires as a data collection technique and two experiments were carried out. The first experiment was to test the effect of product narrative (copy writing), while the second experiment tested the effect of product photo quality on the perception of quality and tourists buying interest. Based on the research conducted, the first experiment shows that the influence of product narrative (copy writing) affects the perception of quality and tourist buying interest. While in the second experiment, through MANCOVA analysis to see the involvement of respondents who chose five-star hotels, there was a significant difference between the two groups of respondents. Respondents in each experimental group have confidence that the perceived quality and purchase intention are higher than in the control group. This study has limitations because it only examines one digital portal, namely AGODA. Several other digital portals, such as traveloka, pegi-pegi, and tiket.com, have differences when compared to AGODA. The implication of this research is that if the influence of product narrative (copy writing) has a big impact on marketing activities, it needs to be developed